Hidradenocarcinoma: A Rare Skin Disease - Aanchal Bhatia; Muskan Tiwari; Gaganpreet Kaur (International Journal of Cell Biology and Cellular Functions, 2024)
Hidradenocarcinoma (HAC) also known as ‘‘sweat gland tumor” is an aggressive, uncommon, highly malignant, adnexal tumor derived from the intradermal duct of eccrine sweat glands. It is said to be aggressive as it has a high risk of local recurrence (50%–75%) and a high potential to metastasize to nearby lymph nodes or to other distant sites. Hidradenocarcinoma has other recognized variants which are known by different names such as Malignant Acrospiroma, Nodular Hidradenocarcinoma, Clear cell Hidradenocarcinoma, Malignant Nodular Hidradenoma, Malignant Clear Cell Hidradenoma, clear cell eccrine carcinoma or simply sweat gland tumor. However, the term Hidradenocarcinoma (HAC) is the recommended name. This malignant tumor arises from the eccrine glands which are located in sun-exposed locations. These malignancies exhibit a high reactivity to eccrine enzymatic stains and their morphologic features are seen under the electron microscope, so that’s why they are known to originate in the sweat glands. The occurrence rate is about 0.001% of all malignant tumors and Hidradenocarcinoma accounts for approximately 6% of malignant eccrine tumors, which in turn are found in 1:13,000 skin biopsies and <0.001% of all skin cancers. They usually appear de novo on healthy skin, or sometimes malignant transformation from their benign form. In 1865, French pathologist Victor Andre Cornil described the first case of sweat gland cancer. Hidradenocarcinoma (HAC) was first reported in 1948 in Brazil and was first described as a clear cell eccrine carcinoma by Keasby and Hadley in 1954. When Keasby first described this tumor in 1954 he found only 3 cases of hidradenocarcinoma among 235 sweat gland tumors.
Keywords: Tumor; carcinoma; hidradenocarcinoma; hidradenoma; malignant